2016
DOI: 10.1007/s11127-016-0330-y
|View full text |Cite
|
Sign up to set email alerts
|

Do direct-democratic procedures lead to higher acceptance than political representation?

Abstract: Are direct-democratic decisions more acceptable to voters than decisions arrived at through representative procedures? We conduct an experimental online vignette study with a German sample to investigate how voters' acceptance of a political decision depends on the process through which it is reached. For a set of different issues, we investigate how acceptance varies depending on whether the decision is the result of a direct-democratic institution, a party in a representative democracy, or an expert committe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 43 publications
0
20
1
Order By: Relevance
“…A recent study in Sweden showed that following a decision on a contested issue using a representative decision-making process, decision losers became less supporting of the political system and this negative effect proved to be remarkably stable over time (Esaiasson et al in press). A recent study that explicitly compares direct and representative processes further corroborates this conclusion (Towfigh et al 2016).…”
Section: Discussionmentioning
confidence: 58%
“…A recent study in Sweden showed that following a decision on a contested issue using a representative decision-making process, decision losers became less supporting of the political system and this negative effect proved to be remarkably stable over time (Esaiasson et al in press). A recent study that explicitly compares direct and representative processes further corroborates this conclusion (Towfigh et al 2016).…”
Section: Discussionmentioning
confidence: 58%
“…For important issues, decision acceptance is greater with direct participation. 88 Increased legitimacy and acceptance of decisions is associated with improved motivation and performance. 89 A lowquality solution that has good acceptance can be more effective than a higherquality solution that lacks acceptance.…”
Section: Z Energy Case: Swarming Enables Convergence On Strategic Primentioning
confidence: 99%
“…When the processes governing political outcomes become contorted or manipulated, trust in government ought to decline. This process-oriented perspective is supported by more recent work on the relationship between scandals and trust (Bowler & Karp, 2004;Chanley, Rudolph, & Rahn, 2000;Orren, 1997), and citizens' level of involvement in the democratic process (Towfigh et al, 2016). Recent work on ideological polarization in legislatures has painted a picture of real distortion in governing processes (Lee, 2015).…”
Section: Process Performance and Political Trustmentioning
confidence: 96%